Hopf Bifurcation Analysis of a Host-Generalist Parasitoid Model with Diffusion Term and Time Delay (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we studied a delayed host-generalist parasitoid modelwith Holling II functional response and diffusion term. The Turing instabilityand local stability are studied. The existence of Hopf bifurcation is investigated, and some explicit formulas for determining the bifurcation direction andthe stability of the bifurcating periodic solution are derived by the theory ofcenter manifold and normal form method. Some numerical simulations arecarried out.
Keywords: Delay; Diffusion; Turing instability; Hopf bifurcation.